2012
DOI: 10.1186/1477-5751-11-14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 60 minutes of hyperoxia followed by normoxia before coronary artery bypass grafting on the inflammatory response profile and myocardial injury

Abstract: BackgroundIschemic preconditioning induces tolerance against ischemia-reperfusion injury prior a sustained ischemic insult. In experimental studies, exposure to hyperoxia for a limited time before ischemia induces a low-grade systemic oxidative stress and evokes an (ischemic) preconditioning-like effect of the myocardium. We hypothesised that pre-treatment by hyperoxia favours enchanced myocardial protection described by decreased release of cTn T in the 1st postoperative morning and reduces the release of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…Two other studies showed a non‐significantly lower or similar cardiac index . Pre‐treatment by 60 or 120 min of hyperoxia did not affect cardiac index .…”
Section: Methodsmentioning
confidence: 78%
See 3 more Smart Citations
“…Two other studies showed a non‐significantly lower or similar cardiac index . Pre‐treatment by 60 or 120 min of hyperoxia did not affect cardiac index .…”
Section: Methodsmentioning
confidence: 78%
“…Animal studies suggest that hyperoxia has favourable effects on myocardial ischaemic injury through a preconditioning effect on cardiac muscle . A similar study in humans, exposing patients to hyperoxia (F I O 2 > 0.96) for 130 and 60 min before coronary artery bypass grafting, had no effect on the cardiac enzymes creatine kinase MB (CK‐MB) and troponin I . However, hyperoxia applied during cardiac surgery, during reperfusion or the entire bypass period increased ischaemia‐reperfusion injury as estimated by troponin T and creatine kinase (Table ).…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…Only five of the reports described how the trials were funded. 1,8,9,26,27 None of these trials were industry supported. The average age of patients included in trial intervention groups ranged from 47 to 68 years ( Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%